The Role of the Solidarity Economy in Strengthening Community Resilience in Post-Social Crisis Contexts - Ester Valerie; Bohuslav Bohuslav (Kampret Journal, 2026)
This study examines the role of the solidarity economy in enhancing community resilience in the aftermath of social crises. In many post-crisis contexts, conventional economic systems have proven insufficient in addressing the complex challenges of economic recovery, social inequality, and weakened community structures. Data are collected through interviews with community members and cooperative leaders, surveys to assess levels of social capital and economic stability, and case studies of selected rural and urban communities affected by social crises. The analysis focuses on three main dimensions: economic impact (income recovery and employment), social impact (trust, cooperation, and participation), and institutional impact (community governance and local organizations). However, challenges such as limited funding, weak policy support, and lack of skills may hinder their sustainability. The research contributes to a more comprehensive understanding of resilience by integrating economic and social perspectives within a unified analytical framework.